ANALISIS DETERMINAN PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) KOTA MATARAM TAHUN 2011-2024 - Aisyah, Laela Ulfi Juianti; Salmah, Emi; Wafik, Ahmad Zaenal (Investama : Jurnal Ekonomi dan Bisnis, 2026)
Regional Original Income (PAD) is a key indicator in measuring the level of fiscal independence of a region. Through Regional Original Income (PAD), local governments can finance various development needs and public services without relying too much on fund transfers from the central government. However, in reality, the potential of Regional Original Income (PAD) in various regions in Indonesia, including Mataram City, remains under-explored. The type of research used in this study is quantitative research using an associative approach. The results show that Regional Expenditure partially has a positive and significant effect on Mataram City's Regional Original Income (PAD), so that increased public spending can encourage increased regional revenue. Meanwhile, Regional Financing and Population have a negative and insignificant effect, indicating that neither has made a real contribution to increasing PAD. Inflation has a positive but insignificant effect, because price increases have not been fully followed by an increase in community economic activity. Simultaneously, the four variables Regional Expenditure, Regional Financing, Inflation, and Population have a significant effect on Regional Original Income (PAD), as shown by the results of the F test. This finding emphasizes the importance of effective expenditure management, optimizing the use of regional financing, controlling inflation, and increasing population productivity to support fiscal independence and increasing Regional Original Income of Mataram City.